Сегментація на акустичні склади для компілятивного синтезу англійського мовлення - Дудник, З. (Лексикографічний бюлетень, 2006)
This paper describes the approach to syllabification currently used in the Laboratory of Computational Linguistics (Kyiv National Linguistic University) for English text-to-speech synthesis. Syllable is a subcomponent of the word model whereas quasi-syllable is a subcomponent of the hierarchic speech model of phonetic word, rhythmical group, and syntagma. The real structure and syntactical position of quasi-syllables enables the TTS-system to retain the naturalness of concatenative speech signals.